A new Platycheirus Le Peletier et Serville, 1828 (Diptera, Syrphidae) species of the manicatus subgroup, from the Taimyr Peninsula (Northern Siberia) - Barkalov, Anatolij V. (Zootaxa, 2013)
A new species of the genus Platycheirus Le Peletier et Serville, 1828 (Diptera, Syrphidae) is described from the Taimyr Peninsula (North of Krasnoyarsk Region). The new species belongs to the manicatus subgroup, being close to P. groen-landicus Curran, 1927, but differing by the narrower angle of approximation of the eyes (approximately equal 90°) and the presence of short black setae on the ventral side of the mid metatarsus. In P. groenlandicus the angle of approximation of the eyes is 120